THE USE OF GUESSING GAME TO ENHANCE STUDENTS’ VOCABULARY MASTERY AT SEVENTH GRADERS OF SMPN 3 CIMAHI - Anisa Razmi; Risma Purnamasari; Iman Santoso (PROJECT (Professional Journal of English Education), 2019)
This research is applied a classroom action research. This research aimed to find out the effectiveness students vocabulary mastery through guessing game in seventh grade of SMP Negeri 3 Cimahi in the school year of 2018/2019. The populations of research are all of the students at seventh-grade in SMP Negeri 3 Cimahi. Method of this research is Classroom Action Research (CAR) applying a qualitative approach. Data sources are informants consist of teachers, students in the seventh grade of SMP Negeri 3 Cimahi and staffs. The data collection techniques are tests, observations, and documentation techniques. The research was taken in two cycles with total meetings were seven; one pre-test, two post-tests and four meetings as treatment. Planning, acting, observation, and reflecting was the steps which carried out in each cycle. The data has been gathered and anaylzed with IBM SPSS Statistics version 22. From pre-test, only 30,5% of students reached Kriteria Ketuntasan Maksimal (KKM), after treatment and post-test 88,8% of students can reach KKM. The improvement of student’s vocabulary results from the application of Guessing Games that helps the students develop their vocabulary memorizing ability with a fun way. The conclusion of the research said: The student’s vocabulary mastery with guessing game improves either individually or classically.